PENGARUH DUKUNGAN SOSIAL DAN GAYA KEPEMIMPINAN PARTISIPATIF TERHADAP KINERJA KARYAWAN PADA DIVISI PEMASARAN PDAM SURYA SEMBADA KOTA SURABAYA - AYU RAMADHANI, FITRI (Jurnal Ilmu Manajemen (JIM), 2018)
Competition in the globalization era requires companies to apply social support and a good leadership style then the work quality of employees can be maintained and obtain superior and quality Human Resources (HR). Employees are an important aspect in developing a company.This study aims to determine how the influence of social support and participatory leadership style on employee performance in the marketing division of PDAM Surya Sembada Surabaya.The population in this study were all employees in the marketing division of 35 employees. Using a multiple linear regression analysis model. The results of this study indicate that social support does not affect employee performance, while the partitionative leadership style influences employee performance. Social support and participatory leadership styles simultaneously affect employee performance. Keywords: employee performance; participatory leadership style; social support